2020
DOI: 10.1016/j.yjsbx.2020.100031
|View full text |Cite
|
Sign up to set email alerts
|

In crystallo-screening for discovery of human norovirus 3C-like protease inhibitors

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Hence, it is neces sary to identify regions that are highly conserved across the different genogroups and are essential for protease activity as potential binding sites for the antivirals. Recently, a study using crystal-based fragment screening has identified 15 inhibitors targeting regions be sides the active site in Southampton protease [104]. The authors identified multiple frag ment-based inhibitors to the regions, including the active site, the RNA-binding site, and the central cavity in the crystallographic tetramer interface.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…Hence, it is neces sary to identify regions that are highly conserved across the different genogroups and are essential for protease activity as potential binding sites for the antivirals. Recently, a study using crystal-based fragment screening has identified 15 inhibitors targeting regions be sides the active site in Southampton protease [104]. The authors identified multiple frag ment-based inhibitors to the regions, including the active site, the RNA-binding site, and the central cavity in the crystallographic tetramer interface.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…The analysis of a MAP-I-bound GI protease provided valuable information about substrate recognition and binding groups and validated rational structure-aided peptide design for anti-protease drug development [16]. Many other examples of inhibitor-bound GI HuNoV protease structures have also been determined, such as those described in references [17][18][19], with 51 crystal structures of GI noroviruses with and without inhibitors bound currently in the Protein Data Bank (PDB). In contrast, there are only two crystal structures of GII.4 proteases available (PDB codes 6NIR and 6B6I) which are both apoenzymes.…”
Section: Introductionmentioning
confidence: 96%
“…SV3CP plays a key role in the processing of a 200 kDa polyprotein encoded by ORF1, which is essential to viral replication, and lacks human homologues, making it an ideal target for diagnosis. 17 The specificity of our designed substrate was examined, and the protease detection limit was determined to be 28.0 nM. Finally, the plasmonic sensing system's performance was tested in relevant biological matrices and had a notable performance in external breath condensate, urine, and 1% fecal matter.…”
Section: Introductionmentioning
confidence: 99%